2016
DOI: 10.1155/2016/8432973
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Knowledge and Current Practice of Pain Assessment and Management: How Much Progress Have We Made?

Abstract: Context. Despite improvement in pain management and availability of clinical treatment guidelines, patients in Jordan are still suffering from pain. Negative consequences of undertreated pain are being recognized as a reason for further illnesses and poor quality of life. Healthcare providers (HCPs) are responsible for relieving pain of their patients. Objective. To evaluate the knowledge and attitudes of HCPs toward pain management in Jordan. Methods. A 16-item questionnaire with agree or disagree options was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 55 publications
9
56
2
Order By: Relevance
“…A study done in the United Kingdom had a comparative cross-sectional study design but our study design was descriptive cross-sectional. e USA study used a mail data collection technique by using 52 items for the assessment of knowledge among 1000 emergency e result of this study also showed that nurses' knowledge towards pain management was higher than that in the studies done in Mekelle, Ethiopia, 58.6% [22], Zimbabwe, 35.5% [16], Iran, 46.6% [23], Turkey, 38.2% [12] and 39.5% [24], Australia, 24% [25] and Malaysia, 25% [4]. e possible justification of this finding which is higher than the above studies might be due to differences in study setting, the difference in sample size, different instruments used, and the difference in the outcome rating they used; for example, in Malaysian study, the knowledge was rated as high, moderate, and low.…”
Section: Knowledge Of the Study Participants About Painmentioning
confidence: 88%
“…A study done in the United Kingdom had a comparative cross-sectional study design but our study design was descriptive cross-sectional. e USA study used a mail data collection technique by using 52 items for the assessment of knowledge among 1000 emergency e result of this study also showed that nurses' knowledge towards pain management was higher than that in the studies done in Mekelle, Ethiopia, 58.6% [22], Zimbabwe, 35.5% [16], Iran, 46.6% [23], Turkey, 38.2% [12] and 39.5% [24], Australia, 24% [25] and Malaysia, 25% [4]. e possible justification of this finding which is higher than the above studies might be due to differences in study setting, the difference in sample size, different instruments used, and the difference in the outcome rating they used; for example, in Malaysian study, the knowledge was rated as high, moderate, and low.…”
Section: Knowledge Of the Study Participants About Painmentioning
confidence: 88%
“…It is therefore important for nurses to select and use appropriate assessment tool for pain management to enhance optimal pain relief [30]. Previous studies [21,31] report of lack of pain assessment tools which were linked to suboptimal pain management of patients. Although any such linkages were beyond the scope of the present study, we believe the absence of pain assessment tools may negatively impact pediatric pain management as pain assessment tools serve as a guide in providing baseline information and serving as a means of evaluating the effectiveness of pain management interventions [32].…”
Section: Discussionmentioning
confidence: 99%
“…This has been conventionally attributed to a variety of obstacles including health professional, patient, and health-care system concerns [2][3][4]. Health-care providers in general, and physicians in particular, have been frequently evaluated in terms of their knowledge, attitude and practice in regards to cancer pain management (CPM) [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%